Non-newtonian momentum transfer past an isothermal stretching sheet with applied suction - Veena, P.H.; Suresh, B.; Pravin, V.K.; Goud, A.M. (Zielona Góra: Uniwersytet Zielonogórski)
The paper discusses the flow of an incompressible non-Newtonian fluid due to stretching of a plane elastic surface in a saturated porous medium in the approximation of boundary layer theory. An exact analytical solution of non-linear MHD momentum equation governing the self-similar flow is given. The skin friction co-efficient decreases with an increase in the visco-elastic parameter k1 and increase in the values of both the magnetic parameter and permeability parameter.
Keywords: non-Newtonian fluid; magnetic field; permeability; effect of viscoelasticity